MEASURING JUSTICE IN THE SETTLEMENT OF KALURAHAN LAND DISPUTES: AN AGRARIAN LAW PERSPECTIVE - Srikusuma, M Rohmidhi; Harve, Renhard (Universitas Muhammadiyah Ponorogo, 2024)
The Special Region of Yogyakarta (DIY) has a special status in land management based on Law No. 13/2012, giving it greater authority in land utilization. Kasultanan and Kadipaten lands are recognized as property rights for the welfare of the community. However, misuse of land licenses has become a serious problem, triggering land conflicts and threatening the environment and the rights of local communities. The research method includes legal (regulatory analysis) and sociological (empirical data) approaches. Primary data was obtained from the community, while secondary data came from legal materials. Case studies were conducted in 4 districts and 1 city in Yogyakarta, focusing on land use permits. Data were collected through document studies, interviews, and observations, then analyzed qualitatively. The research lasted for three months. The origin of land tenure in Yogyakarta dates back to the 1755 Treaty of Gianti, with different histories for Sultanate, Duchy and Kalurahan lands. After independence, Yogyakarta was given agrarian autonomy. Dualism in agrarian law led to uncertainty, triggering corruption and conflict. Regulatory reform, transparency and community participation are needed to address land permit abuse and realize equitable management. The main challenge is the misuse of land licenses, which often involves corruption. Regulatory reform, legal harmonization, institutional strengthening, law enforcement, technology utilization, and strengthening legal culture are needed to address this issue. These efforts aim to realize a fair, transparent and sustainable land management system, involving all relevant parties.